Dual-frequency comb generation with differing GHz repetition rates by parallel Fabry–Perot cavity filtering of a single broadband frequency comb source. (31st May 2016) - Mildner, Jutta; Meiners-Hagen, Karl; Pollinger, Florian
Abstract: We present a dual-comb-generator based on a coupled Fabry–Perot filtering cavity doublet and a single seed laser source. By filtering a commercial erbium-doped fiber-based optical frequency comb with CEO-stabilisation and 250 MHz repetition rate, two broadband coherent combs of different repetition rates in the GHz range are generated. The filtering doublet consists of two Fabry–Perot cavities with a tunable spacing and Pound–Drever–Hall stabilisation scheme. As a prerequisite for the development of such a filtering unit, we present a method to determine the actual free spectral range and transmission bandwidth of a Fabry–Perot cavity in situ . The transmitted beat signal of two diode lasers is measured as a function of their tunable frequency difference. Finally, the filtering performance and resulting beat signals of the heterodyned combs are discussed as well as the optimisation measures of the whole system.